2014
DOI: 10.1111/sjop.12164
|View full text |Cite
|
Sign up to set email alerts
|

Reduced repetition suppression in the occipital visual cortex during repeated negative Chinese personality‐trait word processing

Abstract: Reduced neural activation have been consistently observed during repeated items processing, a phenomenon termed repetition suppression. The present study used functional magnetic resonance imaging (fMRI) to investigate whether and how stimuli of emotional valence affects repetition suppression by adopting Chinese personality-trait words as materials. Seventeen participants were required to read the negative and neutral Chinese personality-trait words silently. And then they were presented with repeated and nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In the present study, the repeated pairs generated lower activation in the occipital cortex, compared to the novel pairs. This result is in agreement with the findings of a previous f MRI study observing that the repetition of items suppressed the occipital visual cortex activity [ 58 , 59 ]. It is reported that such repetition suppression arises from stimulus-specific expectations.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the repeated pairs generated lower activation in the occipital cortex, compared to the novel pairs. This result is in agreement with the findings of a previous f MRI study observing that the repetition of items suppressed the occipital visual cortex activity [ 58 , 59 ]. It is reported that such repetition suppression arises from stimulus-specific expectations.…”
Section: Discussionsupporting
confidence: 93%
“…Research has shown that phonological or semantic repetition can facilitate cognitive processes of Chinese characters in various tasks, such as identification, categorization, lexical decision, and naming task (Neely, 1991;Perfetti & Liu, 2006). The facilitation by phonological or semantic repetition is correlated with reduced neural activities (Qiao, Zheng, Li, Zhu, & Wang, 2014;Schacter, Wig, & Stevens, 2007;Sekiguchi, Koyama, & Kakigi, 2000;Takahiro, Sachiko, & Ryusuke, 2004;Wheatley, Weisberg, Beauchamp, & Martin, 2005). Similar neural repetition suppression has been proposed to explain the temporal repetition compression (Matthews & Gheorghiu, 2016;Pariyadath & Eagleman, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…Functional magnetic resonance imaging (fMRI) has presented a tool for uncovering the underlying brain mechanisms for emotion processing, and previous studies found some emotion-related speci c brain site (Susanne et al, 2019). For example, the amygdala is implicated in fear (Nigel et al, 2021); the cingulate cortex (ACC) involves sadness (P et al, 2018); the inferior temporal gyrus and middle frontal gyrus respond to negative stimuli (Qiao et al, 2014). Although these results were not fully consistent in functional localization between different fMRI, the emotion processing is distributed in distinct brain regions (Simeng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%